2021
DOI: 10.1177/2333794x211019700
|View full text |Cite|
|
Sign up to set email alerts
|

A study of Ophthalmia Neonatorum in the Central Reion of Ghana: Causative Agents and Antibiotic Susceptibility Patterns

Abstract: In developing countries such as Ghana, ophthalmia neonatorum (ON) remains a public health concern. This is because of its unknown etiology patterns, the growing concerns of antibiotic resistance strains and the contribution of ON to childhood blindness. This study was therefore conducted to determine the causative agents, risk factors and the antibiotic sensitivity patterns of micro-organisms associated with ON. A clinic-based prospective study was conducted in the Maternal and Child Health units of 6 health c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…In the present cases, the infection may have started from vertical transmission from the mothers who had a history of UTI and vaginal candidiasis, leading to perinatal infection and, subsequently, ophthalmia neonatorum. 12 Later, the delayed treatment of ophthalmia neonatorum may have contributed to the development of orbital cellulitis. A study conducted in Ilorin found that antenatal maternal vaginal discharge is also one of the predisposing factors of ophthalmia neonatorum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present cases, the infection may have started from vertical transmission from the mothers who had a history of UTI and vaginal candidiasis, leading to perinatal infection and, subsequently, ophthalmia neonatorum. 12 Later, the delayed treatment of ophthalmia neonatorum may have contributed to the development of orbital cellulitis. A study conducted in Ilorin found that antenatal maternal vaginal discharge is also one of the predisposing factors of ophthalmia neonatorum.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Ilorin found that antenatal maternal vaginal discharge is also one of the predisposing factors of ophthalmia neonatorum. 12 …”
Section: Discussionmentioning
confidence: 99%
“…In children, the disease is often caused by Haemophilus influenzae, Streptococcus pneumoniae and Moraxella catarrhalis (Fishovitz et al, n.d.). The course of the disease usually lasts 7 to 10 days the reason for the decline in the clinical scores of conjunctivitis in the rabbits in the control group (Boadi-Kusi et al, 2021). Signs and symptoms include red eye, purulent or mucopurulent discharge, and chemosis (Fishovitz et al, n.d.).…”
Section: Discussionmentioning
confidence: 99%
“…Ophthalmia neonatorum is an ongoing public health problem in countries or settings where prevention strategies are inadequate. [2][3][4][5][6] The etiology of ophthalmia neonatorum is most commonly due to sexually transmitted bacteria such as Neisseria (N.) gonorrhoeae and Chlamydia (C.) trachomatis but could also arise from non-sexually transmitted bacteria or less often from viral and chemical sources. 7 For neonatal conjunctivitis due to sexually transmitted bacteria, the presence of perinatal maternal infection is the predisposing factor.…”
Section: Introductionmentioning
confidence: 99%